IL6R-STAT3-ADAR1 (P150) interplay promotes oncogenicity in multiple myeloma with 1q21 amplification - Phaik Ju Teoh; Tae-Hoon Chung; Pamela Y.Z. Chng; Sabrina H. M. Toh; Wee Joo Chng (Haematologica, 2020)
1q21 amplification is an important prognostic marker in multiple myeloma. In this study we identified that IL6R (the interleukin-6 membrane receptor) and ADAR1 (an RNA editing enzyme) are critical genes located within the minimally amplified 1q21 region. Loss of individual genes caused suppression to the oncogenic phenotypes, the magnitude of which was enhanced when both genes were concomitantly lost. Mechanistically, IL6R and ADAR1 collaborated to induce a hyper-activation of the oncogenic STAT3 pathway. High IL6R confers hypersensitivity to interleukin-6 binding, whereas, ADAR1 forms a constitutive feed-forward loop with STAT3 in a P150-isoform-predominant manner. In this respect, ADAR1-P150 acts as a direct transcriptional target for STAT3 and this STAT3-induced-P150 in turn directly interacts with and stabilizes the former protein, leading to a larger pool of proteins acting as oncogenic transcription factors for pro-survival genes. The importance of both IL6R and ADAR1-P150 in STAT3 signaling was further validated when concomitant knockdown of both genes impeded IL6-induced-STAT3 pathway activation. Clinical evaluation of various datasets of myeloma patients showed that low expression of either one or both genes was closely associated with a compromised STAT3 signature, confirming the involvement of IL6R and ADAR1 in the STAT3 pathway and underscoring their essential role in disease pathogenesis. In summary, our findings highlight the complexity of the STAT3 pathway in myeloma, in association with 1q21 amplification. This study therefore reveals a novel perspective on 1q21 abnormalities in myeloma and a potential therapeutic target for this cohort of high-risk patients.